2014
DOI: 10.1002/ange.201404438
|View full text |Cite
|
Sign up to set email alerts
|

Total Chemical Synthesis of Biologically Active Fluorescent Dye‐Labeled Ts1 Toxin

Abstract: Ts1 toxin is a protein found in the venom of the Brazilian scorpion Tityus serrulatus. Ts1 binds to the domain II voltage sensor in the voltage-gated sodium channel Nav and modifies its voltage dependence. In the work reported here, we established an efficient total chemical synthesis of the Ts1 protein using modern chemical ligation methods and demonstrated that it was fully active in modifying the voltage dependence of the rat skeletal muscle voltage-gated sodium channel rNav1.4 expressed in oocytes. Total s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 23 publications
(20 reference statements)
0
11
0
Order By: Relevance
“…Nor did the folding conditions we had previously developed for Ts1. [12] Addition of 20 % v/v DMSO to the redox buffer gave acceptable yields of discrete folded products of mass 8Dal ess than that of the corresponding polypeptide chains,w hich indicates the formation of four disulfide bonds.A fter careful optimization, the final folding conditions used were:[ polypeptide] 0.02 mg mL À1 ;2 .0 mm GSH/1.0 mm GSSG;0 .5 ml -arginine·HCl;1 .0 mm EDTA; 0.1m Tr is,2 0% DMSO,p H8.5;r oom temperature.D ata for the folding of Ts3(1-64)-CONH 2 are shown in Figure 2b. Using these conditions,w ew ere able to fold all four Ts3 candidate polypeptide chains,with concomitant formation of 4d isulfides in each case as shown by the loss of 8Da.…”
mentioning
confidence: 97%
“…Nor did the folding conditions we had previously developed for Ts1. [12] Addition of 20 % v/v DMSO to the redox buffer gave acceptable yields of discrete folded products of mass 8Dal ess than that of the corresponding polypeptide chains,w hich indicates the formation of four disulfide bonds.A fter careful optimization, the final folding conditions used were:[ polypeptide] 0.02 mg mL À1 ;2 .0 mm GSH/1.0 mm GSSG;0 .5 ml -arginine·HCl;1 .0 mm EDTA; 0.1m Tr is,2 0% DMSO,p H8.5;r oom temperature.D ata for the folding of Ts3(1-64)-CONH 2 are shown in Figure 2b. Using these conditions,w ew ere able to fold all four Ts3 candidate polypeptide chains,with concomitant formation of 4d isulfides in each case as shown by the loss of 8Da.…”
mentioning
confidence: 97%
“…Although isolated from the same scorpion venom, Ts3 and Ts1 toxins are very different protein molecules:t hey have distinct biological activities-Ts1 is ab eta scorpion toxin while Ts3 is an alpha scorpion toxin; there is little sequence homology between the two polypeptide chains (only 16/53 conserved non-Cys residues; Figure 1) and the Ts3 polypeptide chain has much greater structural ambiguity at its Cterminus than was the case with the Ts1 toxin. [12] Although the Ts3 and Ts1 toxins do share aconserved pattern of eight Cys residues in the amino acid sequence of their polypeptide chains (Figure 1), it has been shown that, even where the pattern of Cys residues is conserved, scorpion venom proteins can have distinct tertiary structures. [13] Total chemical synthesis of the candidate Ts3 polypeptide chains was carried out by using amodular approach as shown in Scheme 1b.N ative chemical ligation (NCL) sites were chosen at -Tyr 23 -Cys 24 -a nd -Tyr 46 -Cys 47 -s ot hat, after preparation of the C-terminal peptide variants,t he peptide segments used were of similar length (23;2 3; and 16, 18, 20, or 21 amino acids).…”
mentioning
confidence: 97%
“…We have previously reported total synthesis of the Ts1 toxin protein molecule, [12] but that experience was of limited use for the current work. Although isolated from the same scorpion venom, Ts3 and Ts1 toxins are very different protein molecules:t hey have distinct biological activities-Ts1 is ab eta scorpion toxin while Ts3 is an alpha scorpion toxin; there is little sequence homology between the two polypeptide chains (only 16/53 conserved non-Cys residues; Figure 1) and the Ts3 polypeptide chain has much greater structural ambiguity at its Cterminus than was the case with the Ts1 toxin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Labelling of Cn2 [Q54Pra] was carried out via a slightly modified procedure, published previously (241…”
Section: Click-chemistry Labeling Of Cn2 [Q54pra] With Bodipymentioning
confidence: 99%